SOSIALISASI DAN LOKAKARYA KOMUNIKASI LINGKUNGAN UNTUK KONSUMSI DAN PRODUKSI YANG BERTANGGUNG JAWAB - Lydia Irena; Nathilda Anggraini Fauzi; Cindy Monica; Joanna Aprilia; Felisia Titania; Moira Nikita (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2026)
Environmental issues have evolved into critical global challenges affecting all nations, including Indonesia. One of the significant environmental problems currently faced by Indonesia is waste management. The overflow of waste is primarily caused by irresponsible consumption behaviors, particularly in the use of plastics. This issue has become a focal point for the Indonesian government. The Indonesian government has officially adopted the United Nations' Sustainable Development Goals (SDGs) through Presidential Regulation No. 59 of 2017 on the Implementation of Sustainable Development Goals (SDGs). One of the agendas outlined in the SDGs is Goal No. 12, which focuses on responsible consumption and production. This goal aims to ensure more sustainable global consumption and production patterns, reduce waste, and minimize negative impacts on the environment and natural resources. The partner for this PKM (Community Service Program) initiative is Hati Bangsa Orphanage, a non-profit organization dedicated to caring for orphans and children from underprivileged families. Based on discussions with the partner, the PKM team identified the need for developing soft skills among the children at Hati Bangsa Orphanage, in alignment with the aforementioned Sustainable Development Goals (SDGs). Therefore, the PKM team plans to implement the program titled